Numerical analysis of stability of an axially-compressed i-beam rod subjected to constrained torsion - Amirshokh Kh. Abdurakhmonov (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. Today thin-walled structures are widely used in the construction industry. The analysis of their rigidity, strength and stability is a relevant task which is of particular practical interest. The article addresses a method for the numerical analysis of stability of an axially-compressed i-beam rod subjected to the axial force and the bimoment. An axially compressed i-beam rod is the subject of the study.Materials and methods. Femap with NX Nastran were chosen as the analysis toolkit. Axially compressed cantilever steel rods having i-beam profiles and different flexibility values were analyzed under the action of the bimoment. The steel class is C245. Analytical data were applied within the framework of the Euler method and the standard method of analysis pursuant to Construction Regulations 16.13330 to determine the numerical analysis method.Results. The results of numerical calculations are presented in geometrically and physically nonlinear settings. The results of numerical calculations of thin-walled open-section rods, exposed to the axial force and the bimoment, are compared with the results of analytical calculations.Conclusions. Given the results of numerical calculations, obtained in geometrically and physically nonlinear settings, recommendations for the choice of a variable density FEM model are provided. The convergence of results is estimated for different diagrams describing the steel behavior. The bearing capacity of compressed cantilever rods, exposed to the bimoment, is estimated for the studied flexibility values beyond the elastic limit. A simplified diagram, describing the steel behaviour pursuant to Construction regulations 16.13330, governing the design of steel structures, is recommended to ensure the due regard for the elastoplastic behaviour of steel. The numerical analysis method, developed for axially-compressed rods, is to be applied to axially-compressed thin-walled open-section rods. National Research Moscow State University is planning to conduct a series of experiments to test the behaviour of axially-compressed i-beams exposed to the bimoment and the axial force. Cantilever i-beams 10B1 will be used in experimental testing.